2018
DOI: 10.1371/journal.pone.0206939
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain and deep gray matter atrophy detection over 5 years with 3T MRI in multiple sclerosis using a variety of automated segmentation pipelines

Abstract: BackgroundCerebral atrophy is common in multiple sclerosis (MS) and selectively involves gray matter (GM). Several fully automated methods are available to measure whole brain and regional deep GM (DGM) atrophy from MRI.ObjectiveTo assess the sensitivity of fully automated MRI segmentation pipelines in detecting brain atrophy in patients with relapsing-remitting (RR) MS and normal controls (NC) over five years.MethodsConsistent 3D T1-weighted sequences were performed on a 3T GE unit in 16 mildly disabled patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Atrophy in MS is often considered to be the result of extensive axonal transection and demyelination [21][22][23]. The contribution of neuroglia may be less clear; reactive gliosis has the potential to mask considerable tissue loss in WM lesions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy in MS is often considered to be the result of extensive axonal transection and demyelination [21][22][23]. The contribution of neuroglia may be less clear; reactive gliosis has the potential to mask considerable tissue loss in WM lesions [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Using the MP‐RAGE images, deep GM (thalamus, caudate, GP, and putamen) brain volumes were measured with the automated FMRIB Software Library (FSL‐FIRST) pipeline (v.6.0, https://fsl.fmrib.ox.ac.uk) using previously described methods 21,22 . Whole brain segmentation was also performed from the MP‐RAGE images to measure intracranial volume (ICV) and brain parenchymal fraction (BPF), a normalized estimate of whole brain atrophy using Statistical Parametric Mapping (v.12, https://www.fil.ion.ucl.ac.uk/spm/software/spm12/) 22 . All raw deep brain volumes were normalized into fractions after dividing them by the ICV 23 .…”
Section: Methodsmentioning
confidence: 99%
“…21,22 Whole brain segmentation was also performed from the MP-RAGE images to measure intracranial volume (ICV) and brain parenchymal fraction (BPF), a normalized estimate of whole brain atrophy using Statistical Parametric Mapping (v.12, https://www.fil.ion.ucl.ac.uk/spm/software/spm12/ ). 22 All raw deep brain volumes were normalized into fractions after dividing them by the ICV. 23 BPF was calculated as the sum of the GM and WM volumes divided by the total ICV (the sum of GM, WM, and CSF volumes).…”
Section: Whole Brain and Deep Gm Volumetric Analysesmentioning
confidence: 99%
“…For example, studies have shown that field strength, [9][10][11] type of pulse sequence, 9,[12][13][14] scanner upgrades, 9 scanner vendor, 9,15 and voxel size 13 may each influence MS-related cerebral lesion and atrophy volumetric measures. Furthermore, the type of postprocessing image segmentation pipeline, 12,13,[16][17][18][19][20] preprocessing image preparation and software version within the same pipeline, 9,21 or workstation operating system 21 may also add variation to the results. Even when using a consistent field strength, scanner vendor, and high-resolution harmonized pulse sequences, there is considerable variability in manual and automated segmentation results 22 partly based on hardware factors such as gradient • C 2020 by the American Society of Neuroimaging nonlinearity.…”
Section: Introductionmentioning
confidence: 99%